Being with woman: a creative-critical exploration of midwifery identity and aspects of the mother-midwife relationship. - Grace, Nicola (2024)
This creative-critical thesis is comprised of two sections. The first section is a memoir, titled With Woman: A Memoir of Birth, Death and Midwifery. The second section is a critical commentary, ‘Telling Midwifery and Other Untellable Things Through Memoir’.